2022
DOI: 10.12659/aot.936751
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-Rich Alpha-2-Glycoprotein (LRG-1) as a Potential Kidney Injury Marker in Kidney Transplant Recipients

Abstract: Background Kidney transplantation is the treatment of choice for most patients with end-stage renal disease. To improve patient and transplant survival, non-invasive diagnostic methods for different pathologies are important. Leucine-rich alpha-2-glycoprotein (LRG-1) is an innovative biomarker that is elevated in cases of angiogenesis, inflammation, and kidney injury. However, there are limited data about the diagnostic role of LRG-1 in kidney transplant recipients. The aim of this study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…As aforementioned, LRG1 has been found to serve as an effective biomarker of kidney injury. In line with above findings, Popova et al [45] also reported LRG1 was up in serum and urine of patients with kidney injury induced by kidney transplant (n = 35). A positive correlation was found between serum and urine LRG1 (r = 0.41; 95% CI: 0.09 to 0.66; p = 0.01).…”
Section: Acute Kidney Injurysupporting
confidence: 71%
“…As aforementioned, LRG1 has been found to serve as an effective biomarker of kidney injury. In line with above findings, Popova et al [45] also reported LRG1 was up in serum and urine of patients with kidney injury induced by kidney transplant (n = 35). A positive correlation was found between serum and urine LRG1 (r = 0.41; 95% CI: 0.09 to 0.66; p = 0.01).…”
Section: Acute Kidney Injurysupporting
confidence: 71%
“…In addition to plasma, increased urine LRG1 levels in diabetes is also associated with an increased risk of progression to end stage kidney disease independent of traditional cardiorenal risk factors ( 55 ), and in kidney transplant recipients LRG1 has been considered a potential kidney injury marker that correlates with other tubular injury markers and functional deterioration ( 141 ). These human data support the evidence from experimental studies that LRG1 is an important factor in driving CKD through initial effects on the kidney vasculature and the subsequent fibrotic response.…”
Section: Lrg1 and Chronic Kidney Diseasementioning
confidence: 99%